Comparison between Curvilinear and Rectilinear Grid Based Hydraulic Models for River Flow Simulation. (2016) - Morianou, Giasemi G.; Kourgialas, Nektarios N.; Karatzas, George P.
Abstract: In the present work, the two-dimensional hydraulic models MIKE 21 and MIKE 21C were used in order to simulate the water depth at the downstream section of the Koiliaris River Basin in Crete-Greece. Specifically, an important goal of the present study was the comparison of the widely used MIKE 21 with the MIKE 21C model. The MIKE 21C model has been developed specifically to simulate 2D flows and morphological changes in rivers. It is based on an orthogonal curvilinear grid and comprises two parts: (a) the hydrodynamic part that is based on the Saint-Venant equations and (b) the morphological change part for the simulation of sediment transport. In contrast to model MIKE 21C, the general version of MIKE 21 is based on a rectilinear grid. The difference between the curvilinear and the rectilinear grid is that the curvilinear grid lines follow the bank lines of the river, providing a better resolution of the flow near the boundaries. The water depth results of the two models were compared with field observations and a series of statistical indicators. It was concluded that the curvilinear grid based model results were in better agreement with the field measurements.